[Woman]’s World Portrayed in Literary Works of Jane Austen - Gusti Ayu Praminatih; Homsatun Nafiah (Lingua Cultura, 2018)
The researchers conducted research on Jane Austen literary works since she was a prominent female novelist with mostly discussed novels. The aim of this research was investigating how Jane Austen portrayed [woman] in the18th century through literary works. Six major novels were used as data. Hence qualitative method was employed. The novels were converted using AntConc. Then, the researchers identified the 50 highest collocations of [woman] based on three main categories in part of speech namely adjective, noun, and verb. The results reveal that Jane Austen portrays [woman] in the 18th century with positive and negative aspects; internal and external qualities that reflected through adjectives. Jane Austen often uses concrete and abstract nouns related to domestic property collocated with the word [woman]. Furthermore, the verbs that collocate with [woman] in Jane Austen’s literary works are productive verbs. The researchers find that the adjectives, nouns, and verbs that attach to [woman] in Jane Austen novels are related to the domestic sphere and their quality of being strong, logical, and intellectual.